On the Use of the Wilcoxon Criterion in the Practice of Pedagogical Research - Bondareva, Elena; Mazepa, Elena (Mathematical Physics and Computer Modeling, 2021)
The article discusses the use of nonparametric measures of influence in pedagogical research. The Wilcoxon criterion for comparing indicators obtained as a result of measurements in a connected sample is highlighted. The necessary conditions for the application of the criterion, as well as the advantages of its use are indicated. The possibility of using the Wilcoxon criterion is illustrated by the example of determining the effectiveness of the proposed teaching methodology using the Uchi.ru online platform in educational activities. Most modern studies in the field of pedagogy and psychology, along with qualitative descriptions of the results of the research, actively use quantitative analysis. Last analysis includes processing of the data using methods of mathematical statistics. In order to show the effectiveness of the developed methodology for the learning process, it should be considered as a factor influencing changes in the studied trait. Further study of these changes allows the researcher to determine the statistical reliability (significance) of the influence of the factor under consideration. The subsequent analysis of the reliability of the influence of a particular factor, the comparison of the measure of influence of various factors is carried out using parametric (variance analysis) and nonparametric measures of influence (the sign criterion, the Wilcoxon criterion). This article discusses the use of nonparametric measures of influence in pedagogical research. The Wilcoxon criterion is selected for comparing the indicators obtained as a result of measurement in a connected sample and allowing to diagnose not only the direction of changes, but also their severity. The necessary conditions for the application of the criterion, as well as the advantages of its use, are indicated. The possibility of using the Wilcoxon criterion is illustrated by the example of determining the effectiveness of the proposed teaching methodology using the Uchi.ru online platform in educational activities. Conclusions are made about its inefficiency for mastering the material in mathematics for younger schoolchildren.